2023
DOI: 10.1186/s13690-023-01044-z
|View full text |Cite
|
Sign up to set email alerts
|

A Spatio-temporal Bayesian model to estimate risk and influencing factors related to tuberculosis in Chongqing, China, 2014–2020

Abstract: Background Tuberculosis (TB) is a serious infectious disease that is one of the leading causes of death worldwide. This study aimed to investigate the spatial and temporal distribution patterns and potential influencing factors of TB incidence risk, and to provide a scientific basis for the prevention and control of TB. Methods We collected reported cases of TB in 38 districts and counties in Chongqing from 2014 to 2020 and data on environment, pop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several clinical risk factors, including lower CD4 + T-cell counts, CD4/CD8 ratio, higher viral load (VL), and shorter intervals between ATT and ART, have been associated with the development of paradoxical TB-IRIS [ 13 , 14 ]. However, it’s noteworthy that not all PLHIV with TB under similar conditions develop paradoxical TB-IRIS [ 15 – 17 ]. Furthermore, in the current era, the introduction of integrase strand transfer inhibitor (INSTI)-based ART regimens, known for their rapid recovery of CD4 + T-cell counts and VL reduction, raises questions regarding the potential increase in the incidence of paradoxical TB-IRIS.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical risk factors, including lower CD4 + T-cell counts, CD4/CD8 ratio, higher viral load (VL), and shorter intervals between ATT and ART, have been associated with the development of paradoxical TB-IRIS [ 13 , 14 ]. However, it’s noteworthy that not all PLHIV with TB under similar conditions develop paradoxical TB-IRIS [ 15 – 17 ]. Furthermore, in the current era, the introduction of integrase strand transfer inhibitor (INSTI)-based ART regimens, known for their rapid recovery of CD4 + T-cell counts and VL reduction, raises questions regarding the potential increase in the incidence of paradoxical TB-IRIS.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian spatiotemporal models have been applied to study tuberculosis in various countries, including India [134], China [135][136][137], Kenya [138], Indonesia [139], Ethiopia [140]. Srinivasan and Venkatesan [134] examined disease rates among Indian states, assessing neighbourhood tuberculosis infections and their causes using Bayesian models with a CAR approach for spatial and temporal pattern changes in two survey periods.…”
Section: Tuberculosismentioning
confidence: 99%
“… 11 Chen et al reported that the high-risk areas of TB were distributed in the southeast and northeast of Chongqing, China, which might be related to the more aging and empty-nesting population and lower economic levels. 12 The Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) epidemic affects the transmission dynamic of TB. 13 There is a strong synergy between HIV and TB infection.…”
Section: Introductionmentioning
confidence: 99%